(Pro)renin receptor/ATP6AP2 is required for autophagy and regulates proliferation in lung adenocarcinoma cells. (4th November 2020) - Ohba, Koji; Endo, Moe; Sato, Shigemitsu; Kashio‐Yokota, Yurina; Hirose, Takuo; Takahashi, Kazuhiro
Abstract: (Pro)renin receptor ((P)RR)/ ATP6AP2 (ATPase, H + transporting, lysosomal accessory protein 2) functions as an essential accessory subunit of vacuolar H + ‐ATPase (V‐ATPase). V‐ATPase is necessary for lysosome function and autophagy. Autophagy is related to cell proliferation, migration and invasion of various cancer cells. In this study, we aim to clarify the relationship between (P)RR and autophagy in lung adenocarcinoma. Expression of (P)RR and Ki‐67 (a proliferation marker) was studied in sixty‐four adenocarcinoma cases by immunohistochemistry. Lung adenocarcinoma cell line, A549, was transfected with (P)RR‐specific siRNA. Autophagy inhibitors, bafilomycin A1 and chloroquine, were used as positive controls. Cell proliferation and migration were measured by WST‐8 assay and wound healing assay. Autophagosome markers, p62 and LC3, were analyzed by RT‐qPCR, Western blot and immunocytochemistry. Immunohistochemistry showed that (P)RR was expressed in all adenocarcinoma tissues. The intensity of (P)RR immunoreactivity was significantly associated with Ki‐67. Treatment of (P)RR‐specific siRNA suppressed (P)RR expression and significantly reduced cell proliferation and migration as did the autophagy inhibitors. Western blot and immunocytochemistry showed that (P)RR‐specific siRNA, as well as the autophagy inhibitors, induced p62 and LC3 accumulation in cytoplasmic granules. These results suggest that (P)RR is involved in cell proliferation and progression of lung adenocarcinoma via regulating autophagy. Abstract : Suppression of (pro)renin receptor by siRNA significantly reduced the cell number of A549 lung adenocarcinoma cells, accompanied with a reduced expression of Ki‐67 (a proliferation marker) and an increased expression of cleaved‐PARP (an apoptosis marker). Autophagy inhibitors, bafilomycin A1 and chloroquine, similarly reduced the cell number of A549 lung adenocarcinoma cells. (Pro)renin receptor may be involved in cell proliferation and progression of lung adenocarcinoma via regulating autophagy.